2022
DOI: 10.21203/rs.3.rs-1875378/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drops of capillary blood are not appropriate for hemoglobin measurement with HemoCue: A comparative study using drop capillary, pooled capillary, and venous blood samples

Abstract: Background: Population-based surveys matched by time and in the same country, but which use different methodologies for determining hemoglobin (Hb) concentration, have shown inconsistencies in estimating anemia prevalence. This study aims to estimate measurement errors in Hb using the HemoCue 201+ in capillary blood, both in drops and pooled, compared with venous blood analyzed both with the HemoCue 201+ and clinical methodologies as references. Methods: 149 participants (children, women, and older adults) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The Mission® Hb device used in this evaluation is a point-of-care device which uses capillary blood. A study in Malaysia showed that the Mission® Plus Hb device underestimated hemoglobin relative to the gold standard cyanmethemoglobin method (31), which would result in an over-estimation of anemia prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…The Mission® Hb device used in this evaluation is a point-of-care device which uses capillary blood. A study in Malaysia showed that the Mission® Plus Hb device underestimated hemoglobin relative to the gold standard cyanmethemoglobin method (31), which would result in an over-estimation of anemia prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…12 • 04088 14 www.jogh.org • doi: 10.7189/jogh.12.04088 capillary vs venous blood in women [14,16,28,29]. Some studies note that capillary drop-to-drop variability in haemoglobin measurement is higher than for pooled capillary or venous blood samples [30]. Higher variability can bias estimates of the population prevalence anaemia even when mean haemoglobin is unbiased, with the prevalence estimates being more affected when the haemoglobin threshold is further from the population mean.…”
Section: Differences By Type Of Blood Collectionmentioning
confidence: 99%